Implementasi Rencana Pelaksanaan Pembelajaran (Rpp) Satu Lembar Di Sekolah Yayasan Kanaan Nusantara Ungaran - Zega, Berkat Karunia; Oci, Markus; Hapsarini, Deslana R. (Jurnal Lentera Nusantara, 2023)
In schools under the auspices of the Kanaan Nusantara Ungaran Foundation, where each teacher is expected to prepare a Learning Implementation Plan (RPP) before teaching. The cause of the teaching and learning process not running effectively in this school is the lack of teacher preparation in teaching including the preparation of lesson plans. The result is that the achievement of teaching objectives is not optimal. The purpose of writing this research is to find out the implementation and out the results of implementing a one sheet lesson plan in implementing at Kanaan elementary - vocational school. The type method used in this research is descriptive qualitative research method. Data collection techniques with field observations and interviews. The results of implementing a one sheet lesson plan was very effective for use in the learning process. This is evident from the teachers responses of Kanaan elementary school, junior and vocational school when implementing learning using a one sheet lesson plan. So the Implementation of the One Sheet lesson plan is not problematic and very effective to implement in carrying out the learning process in Kanaan elementary - vocational schools.AbstrakDi sekolah di bawah naungan Yayasan Kanaan Nusantara Ungaran, dimana setiap guru diharapkan untuk menyiapkan Rencana Pelaksanaan Pembelajaran (RPP) sebelum mengajar. Penyebab proses belajar mengajar tidak berjalan efektif  di sekolah ini yaitu kurangnya persiapan guru dalam mengajar termasuk juga dalam pembuatan RPP. Akibatnya adalah pencapaian tujuan pengajaran tidak maksimal. Tujuan dari Penulisan penelitian tersebut yaitu untuk mengetahui Implementasi dan hasil dari Implementasi rencana pelaksanaan pembelajaran (RPP) satu lembar dalam pelaksanaan pembelajaran di unit sekolah SD, SMP dan SMK Kanaan Ungaran.Jenis metode yang digunakan dalam penelitian ini yaitu Metode Penelitian kualitatif deskriptif. Teknik pengumpulan datanya dengan observasi lapangan dan wawancara. Hasil dalam pelaksanaan penelitian ini yaitu implementasi RPP satu lembar sangat efektif untuk digunakan dalam proses pembelajaran. Hal ini terbukti dari respon guru-guru SD - SMK Kanaan ketika melaksanakan pembelajaran dengan menggunakan RPP satu lembar.